Exploring risks in the adoption of business intelligence in SMEs using the TOE framework - Ana-Marija Stjepić; Mirjana Pejić Bach; Vesna Bosilj Vukšić (Journal of Risk and Financial Management, 2021)
The business success of small- and medium-sized enterprises (SMEs) increasingly relies on the adoption of various technological innovations. For today's unpredictable business operations, business intelligence systems (BISs) represent one of the most prominent tools with a significant impact on business performance. However, different internal and external risks may influence BIS adoption. The goal of this paper is to investigate the risks that impact BIS adoption in SMEs, using the Technology, Organization, and Environment (TOE) framework. For that purpose, we develop the logistic regression model, using data collected by a questionnaire survey using a sample of 100 Croatian SMEs. The results indicate the applicability of the TOE theoretical framework for examining BIS adoption in SMEs. Given the results obtained, the sampled SMEs should take into account the internal risks related to the organizational dimension and external risks related to the environmental dimension. Our research did not reveal the significant impact of technological risks that encompass characteristics of considered technological innovation related to the technology dimension.
Keywords: 330; adoption; business intelligence systems; risk; TOE framework